Body privacy in gynecology obstetrics - Değirmen, Nuriye; Şaylıgil, Ömür (Acta Bioethica, 2020)
This study aimed to develop a scale to ethically evaluate the privacy of the body in gynecology and obstetrics. It was carried out in a university research and application hospital and in a private hospital in Turkey. A stratified sample was adopted with a total of 2,159 participants, including physicians, nurses, and midwives, OB/GYN patients, surgical patients, internal medicine patients, and healthy individuals. The Lawshe method was used. The results showed that physical space is important in protecting privacy; the participants perceived privacy as a right; women, married people, primary school graduates, older people and those closest to rural culture are more sensitive to privacy than others; Among healthcare providers, physicians are more privacy conscious than nurses and midwives; no participant had in-depth knowledge of patient rights and relevant legislation.The body privacy scale in gynecology and obstetrics proved to be a valid and reliable scale. With it, the privacy of the body in obstetrics and gynecology can be evaluated in future research, as well as the perceptions of body privacy of those who receive and provide medical care. By applying this scale, the privacy of gynecological and obstetric patients can be protected and the results reflected in clinical practice. This scale can also be used in education and in improving ethical sensitivity in physicians.